STUDIES ON HAEMOLYMPH METABOLITE CONCENTRATION IN THE DIFFERENT LARVAL AND PUPAL STAGES OF RHYNCHOPHOROUS FERRUGINEUS - THOMAS, ANNIE; NAIR, C. R.M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The concentration of total protein and total lipid in the haemolymph of the red palm weevil, Rhynchophorus ferrugineus shows that these metabolites in the 20 day old larva was at a low level and increased steadily through 40 day old larva and 60 day old larva. The concentration of these metabolites was still higher in pupa. A statistically significant difference was noted in the haemolymph protein and lipid concentration between these four stages (p<0.001). An increase in the concentration of total sugars was noted through the various larval stages, beginning from the 20 day old larva, 40 day old larva and 60 day old larva. However there was a steep decline in the sugar concentration in pupa. There was significant difference in the haemolymph sugar concentration between the four stages(p<0.05).